Talqiyan Fikriyan dalam Pendidikan Islam: Tinjauan Literatur Sistematis - Nurfazri, Muhammad; Lukman, Fahmy (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the implementation of the Talqiyan Fikriyan method across various educational levels, explore its implementation strategies, and identify its impact on students’ morals, character, and learning motivation. This research employed a Systematic Literature Review (SLR) method following the PRISMA guidelines. Literature searches were conducted across several databases: ERIC, ScienceDirect, DOAJ, Scopus (via Publish or Perish), Google Scholar, and ProQuest, covering publications from January 2021 to June 2025. Out of 24 identified articles, seven met the criteria relevant to the research topic. The results indicated that the application of Talqiyan Fikriyan was often combined with various other learning approaches at different levels of Islamic education. Additionally, Talqiyan Fikriyan contributed to the development of students’ logical, analytical, and solution-oriented thinking skills. In terms of morals and character, this method effectively shaped individuals to be honest, responsible, empathetic, and possess noble character. Moreover, the implementation of this method also encourages an increase in students’ learning motivation, as pupils demonstrated enthusiastic, active, and confident attitudes during learning activities. The learning environment created through this method fosters an enjoyable and conducive atmosphere for students’ intellectual and spiritual development. These findings suggest that the Talqiyan Fikriyan method has the potential to become an effective learning model in Islamic education, cultivating intelligent and well-characterised future generations.